2022
DOI: 10.1002/jcc.26991
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of ligand dissociation kinetics from the protein kinase PYK2

Abstract: Early-stage drug discovery projects often focus on equilibrium binding affinity to the target alongside selectivity and other pharmaceutical properties. The kinetics of drug binding are ignored but can have significant influence on drug efficacy. Therefore, increasing attention has been paid on evaluating drug-binding kinetics early in a drug discovery process. Simulating drug-binding kinetics at the atomic level is challenging for the long time scale involved. Here, we used the transition-based reweighting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…TICA and it variants have been used to study molecular kinetics [17,172,173], free-energy estimation, finding slow CVs [8,56,159,174], enhanced sampling [166,168,169], and analysis of complex processes [160,[175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. For more applications, we refer to reviews [192][193][194].…”
Section: Applicationsmentioning
confidence: 99%
“…TICA and it variants have been used to study molecular kinetics [17,172,173], free-energy estimation, finding slow CVs [8,56,159,174], enhanced sampling [166,168,169], and analysis of complex processes [160,[175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. For more applications, we refer to reviews [192][193][194].…”
Section: Applicationsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been effective in studying the binding and unbinding dynamics of protein–-inhibitor complexes and can be used for kinetic estimates. Understanding the receptor–ligand binding and unbinding process can be useful for drug discovery and development, especially in accelerating lead optimization efforts and lowering drug attrition rates. The bimolecular association rate constant ( k on ) and the dissociation rate constant ( k off ) are required to describe the kinetic profile of a potential noncovalent inhibitor or a drug molecule. Recently, drug–target residence time (1/ k off ), or the time spent by the drug in the binding pocket of the protein, has received significant attention as drugs with a higher residence time are shown to have greater in vivo efficacy as compared to thermodynamic parameters such as free energy. It is possible for drugs with similar binding free energies (Δ G bind ) to have different binding and unbinding kinetic rates.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Furthermore, TRAM have been utilized for thermodynamics and kinetics estimations of ligand (un)binding for kinase and Serine protease. 48,51 To implement TRAM for our study, extensive sampling of the (un)binding process of both ligands was performed using a combination of umbrella sampling and unbiased simulations from the pathway obtained using metadynamics (see Methods section). 52 We showed that TRAM can produce consistent kinetic estimation with less unbiased simulation data compared to traditional methods like the Markov state model.…”
Section: Introductionmentioning
confidence: 99%